Attitudes of South African oral hygienists towards compulsory community service - A Bhayat (Journal compilation 2008 Blackwell Munksgaard, 2008)
Compulsory Community Service (CCS) was introduced into the health service by the government to address the shortage and maldistribution of health professionals within the public sector.